THE EFFECTIVENESS OF PROJECT BASED LEARNING THROUGH MIND-MAPPING PROCESS TO IMPROVE STUDENTS’ VOCABULARY - Nur Halisa Indah Safitri; Santi Andriyani (Jurnal Muara Pendidikan, 2025)
Many of students require aid in order to expand and enhance their vocabulary. Conventional techniques of teaching vocabulary are sometimes difficult and uninteresting for students. The goal of this study is to evaluate how well project-based learning using a mind-mapping process improves seventh-grade students at SMP Ma'arif Tegalsambi's command of English vocabulary. A pre-experimental methodology was used in this study, with one group pre-test and post-test design. The population in this research was 61 students, while the sample were 30 students from class 7A. the data collection tools were the pre-test and post-test, which comprised 25 valid multiple-choice questions. To verify the hypothesis' accuracy, the researchers utilized SPSS software's paired sample T-test feature. The pre-test mean was 59.73, and the post-test mean was 85.73. Thus, it can be concluded that project-based learning using the mind mapping process can help boost students' excitement, so it can improve seventh-grade students' vocabulary mastery at SMP Ma'arif Tegalsambi.